2021
DOI: 10.1186/s42836-020-00066-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of a modular hip dual-mobility articulation in patients with high risk of dislocation: a relatively small-sized acetabulum in Asian patients may limit its use

Abstract: Background Dual-mobility hip component is widely used in Europe and North America, because it effectively reduces hip dislocation in primary and revision total hip arthroplasties. However, reports were limited on the use of dual-mobility articulation in Asian populations. Purpose The aim of this retrospective study was to review the use of modular dual-mobility hip articulation in Asian patients with the high risk factor for hip dislocation. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, no patients required revision procedures for adverse local tissue reaction (ALTR), and ion levels decreased with follow-up, although data on long-term outcomes (> 2 years follow-up) was not reported. 23 Another systematic review by French et al 28 reported that the incidence of clinically significant elevated serum cobalt or chromium ion levels 1 µg/L or higher was 7.9%, and 7µg/L or higher was 1.8% over 279 cases in seven studies following MDM implantation. 24 As mentioned previously, there were two cases of rTHA reported in our study for complications related to metallosis, indicating that although ion levels in the short term may not be of concern, continued surveillance is needed in order to properly understand the risk of metallosis as a complication of MDM implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no patients required revision procedures for adverse local tissue reaction (ALTR), and ion levels decreased with follow-up, although data on long-term outcomes (> 2 years follow-up) was not reported. 23 Another systematic review by French et al 28 reported that the incidence of clinically significant elevated serum cobalt or chromium ion levels 1 µg/L or higher was 7.9%, and 7µg/L or higher was 1.8% over 279 cases in seven studies following MDM implantation. 24 As mentioned previously, there were two cases of rTHA reported in our study for complications related to metallosis, indicating that although ion levels in the short term may not be of concern, continued surveillance is needed in order to properly understand the risk of metallosis as a complication of MDM implants.…”
Section: Discussionmentioning
confidence: 99%
“…21 Based upon the literature as well as the results reported in this study, it appears as though MDM cups remain an excellent choice when evaluating THA patients at high risk of instability or following dislocation. [22][23][24] A well-documented concern is that the use of a cobaltchromium DM acetabular liner on a titanium shell increases the risk of corrosion and resultant metal ion release. 25,26 This corrosive phenomenon is believed to be related to extensive micromotion between the two metal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first total hip arthroplasty (THA) in 1891, significant changes have been made to the design of the bearing surfaces [ 1 ]. Bousquet et al proposed a concept of dual-mobility (DM) in 1974 to improve hip stability by increasing the femoral head-to-neck ratio [ 2 , 3 ]. Since it was first proposed, DM liners have gained popularity in the primary and revision hip arthroplasty settings as a potential tool to help prevent instability events [ 4 ].…”
Section: Introductionmentioning
confidence: 99%